Massage Therapy and Canadians’ Health Care Needs 2020: Proceedings of a National Research Priority Setting Summit - Dryden, Trish (Multimed Inc., 2014)
BACKGROUND: The health care landscape in Canada is changing rapidly as forces, such as an aging population, increasingly complex health issues and treatments, and economic pressure to reduce health care costs, bear down on the system. A cohesive national research agenda for massage therapy (MT) is needed in order to ensure maximum benefit is derived from research on treatment, health care policy, and cost effectiveness. SETTING: A one-day invitational summit was held in Toronto, Ontario to build strategic alliances among Canadian and international researchers, policy makers, and other stakeholders to help shape a national research agenda for MT. METHOD: Using a modified Delphi method, the summit organizers conducted two pre-summit surveys to ensure that time spent during the summit was relevant and productive. The summit was facilitated using the principles of Appreciative Inquiry which included a “4D” strategic planning approach (defining, discovery, dreaming, designing) and application of a SOAR framework (strengths, opportunities, aspirations, and results). PARTICIPANTS: Twenty-six researchers, policymakers, and other stakeholders actively participated in the events. RESULTS: Priority topics that massage therapists believe are important to the Canadian public, other health care providers, and policy makers and massage therapists themselves were identified. A framework for a national massage therapy (MT) research agenda, a grand vision of the future for MT research, and a 12-month action plan were developed. CONCLUSION: The summit provided an excellent opportunity for key stakeholders to come together and use their experience and knowledge of MT to develop a much-needed plan for moving the MT research and professionalization agenda forward.